Congenital pouch colon with rectal atresia revisited - Praveen Mathur; Rahul Gupta; Pradeep Kumar Gupta (Wolters Kluwer Medknow Publications, 2017)
We are adding two cases of congenital pouch colon with rectal atresia (RA) to the already published five cases. The presentation of RA is often delayed owing to the presence of normal anus, however, clinical evaluation, plain abdominal radiograph, and urine examination for meconuria, may help in detecting this rare association early.